Biocementation of fine-grained soil - Ong, Jun Hao (2017)
This report presents an experimental study on the effect of Biopolymer (Xanthan gum and Gellan gum) and Microbiologically Induced Calcite Precipitation (MICP) treatment of compacted finegrained soil. The compaction is conducted using static compaction, standard or modified Proctor compaction and the mechanical strength properties of the biotreated soil were tested with various laboratory tests including: the Triaxial (Unconsolidated Undrained) Test, the Unconfined Compression Test and the California Bearing Ration Test. The purpose for this study is to explore the usage of an environmentally friendly soil improvement method on clayey fill which has multiple applications in civil construction. Xanthan gum treatment to the soil displayed a less compacted density despite having higher UC strength of around 1550 kPa with respect to 800 kPa from the untreated samples. Gellan gum shows little to no improvement in both compaction and UC strength which is likely due to low dosage amount. The MICP treated soil shows a higher dry density after compaction and a higher UC strength of 1300 kPa to 1400 kPa in the dried state as well as compacted state. However, the California Bearing Ratio tests did not show improvement for samples tested immediately after compaction. Further studies are required to understand the mechanisms of the MICP treatment for fine-grained soil.